Pemodelan Persamaan Struktural : Penerapan Manajemen Pengetahuan Dan Faktor-Faktor Pendukungnya - Wajdi, Farid; Wibowo, RB. Tri Joko (Jurnal Teknik Industri, 2017)
The application of knowledge management in an organization requires the enabler factors that should be identified of its readiness before implementation. This study examined knowledge management implementation model with the variables of organizational leadership, culture, and structure as predictor of technology infrastructure variable. The purpose of this study was to examine the fitness of the proposed model with data in the field, as well as to know the relationship between these factors. Data were collected through questionnaire using likert scale 1-5 on 112 respondents from a manufacturing company in Cilegon, Banten. Modeling was done using residual correlation and regression of knowledge sharing indicators and indicator of knowledge management team function. It showed the appropriate result but not yet reached the expected value of Chi-Square of 73.502 with p = 0.010, GFI = 0.907, RMSEA = 0.069, AGFI = 0.848, and RMR = 0.041. Overall the modified model shows results that match the criteria of Goodness of Fit. The results of model analysis also showed that there was an indirect influence of leadership variables on technology infrastructure, through cultural mediators and organizational structures, but direct influence of the leadership on the technology infrastructure was not explained.